Influencing air connectivity outcomes - Guillaume Burghouwt (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2017)
The aviation network plays an important role in today's globalised society. There is a growing understanding among governments worldwide that air connectivity is an asset improving the global competitiveness of cities, regions and countries. Connectivity growth decreases travel costs for consumers and businesses and facilitates global contacts and trade. There is increasing evidence that air connectivity growth stimulates productivity, R&D, foreign direct investment and fosters trade specialisation. Against this background, many governments try to formulate (aviation) policies to influence/enhance connectivity outcomes, so as to achieve a connectivity portfolio that best meets society's needs. This seems to be particularly an issue when airport capacity is scarce or when new airports are added to an existing airport system. Hence, the ITF posed the question how governments can influence connectivity outcomes. To answer this question, we first discuss the concept of air connectivity, the economic value of connectivity and its determinants. We then identify the instruments that can potentially be part of the government's "toolkit" to influence connectivity outcomes. Finally, we discuss two approaches that governments may follow when influencing connectivity outcomes: a market-based approach and an interventionist, administrative approach. We discuss the pros and cons of both approaches and argue that governments should be modest about steering connectivity outcomes using an administrative approach. This paper is focused on the European context in terms of the specific policy instruments that are discussed. However, the insights derived from this paper are likely to apply for other regions as well.
Keywords: 330; Passagierluftverkehr; Verkehrsaufkommen; Luftverkehrspolitik; Europa